Advancing ethnobiology for the ecological transition and a more inclusive and just world: a comprehensive framework for the next 20 years - Albuquerque, Ulysses Paulino; Maroyi, Alfred; Ladio, Ana H.; Pieroni, Andrea; Abbasi, Arshad Mehmood; Toledo, Bárbara Arias; Dahdouh-Guebas, Farid; Hallwass, Gustavo; Soldati, Gustavo Taboada; Odonne, Guillaume; Vandebroek, Ina; Vallès, Joan; et al. (Journal of ethnobiology and ethnomedicine, 2024)
This opinion piece, written by ethnobiologists from different parts of the world, emphasizes the importance of ethnobiology research in advancing contemporary biology, natural resource management, biodiversity conservation, sustainable development, and, especially, contributing to the ecological transition and more just and inclusive world. To achieve these goals, it is essential to develop research and collaborate with social groups that live in close relationship with nature in research activities, such as Indigenous Peoples and Local Communities (IPLC), as well as Afro-descendants and other Marginalized, Minority or Minoritized Communities (AMMC). Ethnobiology can identify and provide locally appropriate solutions to local problems, enabling sustainable resource management at the landscape level. The text explores important aspects that need to be considered to guide the future of ethnobiology in the next 20 years, aiming to integrate and amplify previous discussions held in the discipline and identify points that demand ongoing attention. This paper highlights reflections from diverse researchers, emphasizing how ethnobiology can embrace different perspectives and employ rigorous analysis of complex phenomena toward effective policies and practices. This approach holds the potential to address the challenges the planet is currently facing in the coming decades.